Magnetite nanoparticles grafted with murexide-terminated polyamidoamine dendrimers for removal of lead (II) from aqueous solution: synthesis, characterization, adsorption and antimicrobial activity studies - Ekinci, Selma; Ilter, Zulfiye; Ercan, Selami; Cinar, Ercan; Cakmak, Resit (Elsevier Sci Ltd, 2021)
In this study, new, efficient, eco-friendly and magnetically separable nanoadsorbents, MNPs-G1-Mu and MNPsG2-Mu, were successfully prepared by covalently grafting murexide-terminated polyamidoamine dendrimers on 3-aminopropyl functionalized silica-coated magnetite nanoparticles, and used for rapid removal of lead (II) from aqueous medium. After each adsorption process, the supernatant was successfully acquired from reaction mixture by the magnetic separation, and then analyzed by employing ICP-OES. Chemical and physical characterizations of new nanomaterials were confirmed by XRD, FT-IR, SEM, TEM, and VSM. Maximum adsorption capacities (qm) of both prepared new nanostructured adsorbents were compared with each other and also with some other adsorbents. The kinetic data were appraised by using pseudo-first-order and pseudo-second-order kinetic models. Adsorption isotherms were found to be suitable with both Langmuir and Freundlich isotherm linear equations. The maximum adsorption capacities for MNPs-G1-Mu and MNPs-G2-Mu were calculated as 208.33 mg g(-1) and 232.56 mg g(-1), respectively. Antimicrobial activities of nanoparticles were also examined against various microorganisms by using microdilution method. It was determined that MNPs-G1-Mu, MNPs-G2-Mu and lead (II) adsorbed MNPs-G2-Mu showed good antimicrobial activity against S. aureus ATTC 29213 and C. Parapsilosis ATTC 22019. MNPs-G1-Mu also showed antimicrobial activity against C. albicans ATTC 10231.
Keywords: Nanoparticles; Polyamidoamine dendrimers; Murexide; Adsorption; Antimicrobial activity